Feeding Deterrence Activity of Momordica cymbalaria Fenzl ex Hook Leaf, Fruit Skin, Seed and Tuber Extract against Spodoptera litura Fabricius - ADAIKKAN, YOGAPRIYA; THIRUNAVUKKARASU, SELVAMUTHUKUMARAN (Research Perspective on Biological Science Vol. 2, 2025)
Spodoptera litura Fab. (Beet armyworm; Tobacco cutworm), a devastating polyphagous pest known to cause cent percent yield loss under outbreak conditions, is regularly managed using chemical insecticides and has developed multi-pronged resistance. Plant secondary metabolites exhibit a wide range of biological activity and may act as feeding and oviposition deterrents, repellents, fumigants, and behavior modifiers. Fruits and tubers of Momordica cymbalaria Hook (Fenzl.) possess anti-ovulatory and abortifacient properties that could be exploited in the management of insect pests. Hence, the feeding deterrent activity of M. cymbalaria leaf, peel (fruit skin), seed, and tuber solvent extract against Spodoptera litura Fabr. was studied. The present study was carried out from 2019 to 2022 in the Phyto-insecticide Laboratory, Department of Entomology, Faculty of Agriculture, Annamalai University, Annamalainagar, Tamil Nadu, India. Different concentrations of acetone extract of leaf from 0.3% to 0.8% performed better in deterring S. litura larval feeding. Peel acetone extract showed a strong feeding deterrence (94.83% leaf area protection over the absolute control) at 0.9% concentration, followed by medium deterrence at 0.8, 0.7, and 0.6% concentrations (85.62, 77.90, and 67.08 % protection, respectively). The hexane seed extract was comparatively oilier and had a distinct rancid smell noticeable in the higher concentrations (0.8, 0.9, and 1%). Tubers did not exhibit any significant leaf area protection below 0.2% concentration. However, 1% tuber acetone extract showed 99.36 percent protection. The effective concentrations of leaf acetone extract for 50 and 95% deterrence were 0.27 and 0.84 percent, respectively. The effective concentrations of other plant parts were ranked as follows: Seeds>Peels>Tubers. Therefore, it is stated that M. cymbalaria possesses very effective feeding deterrence activity against the common cutworm S. litura.